Gad1‐promotor‐driven GFP expression in non‐GABAergic neurons of the nucleus endopiriformis in a transgenic mouse line. Issue 14 (20th March 2019) - Riedemann, Sophie; Sutor, Bernd; Bergami, Matteo; Riedemann, Therese
Abstract: Transgenic animals have become a widely used model to identify and study specific cell types in whole organs. Promotor‐driven reporter gene labeling of the cells under investigation has promoted experimental efficacy to a large degree. However, rigorous assessment of transgene expression specificity in these animal models is highly recommended to validate cellular identity and to isolate potentially mislabeled cell populations. Here, we report on one such mislabeled neuron population in a widely used transgenic mouse line in which GABAergic somatostatin‐expressing interneurons (SOM pos INs) are labeled by eGFP (so‐called GIN mouse, FVB‐Tg(GadGFP)45704Swn/J). These neurons represent a subpopulation of all SOM pos INs. However, we report here on GFP labeling of non‐GABAergic neurons in the nucleus endopiriformis of this mouse line. Abstract : We investigated the properties of a neuron population in a widely used transgenic mouse line in which somatostatin‐expressing interneurons (SOM pos INs) are labeled by eGFP (so‐called GIN mouse, FVB‐Tg(GadGFP)45704Swn/J). This population of GFP‐expressing (GFP pos ) neurons was located in the nucleus endopiriformis of this mouse line. Surprisingly, GFP pos neurons within this brain area had no anatomical or electrophysiological resemblance to SOM pos INs of the other cortical brain areas but seemed more related to pyramidal neurons. Moreover, the great majority of these GFP pos neurons expressed neither somatostatin nor γ‐amino‐butyric‐acid.